Relationship between Bank Customer Retention Strategies and Customer Satisfaction in Commercial Banks in Machakos Town - Kavita, Patricia; Wamitu, Susan; Nzomoi, Joseph (European Journal of Business and Strategic Management, 2022)
Purpose: this study was to investigate the relationship between service quality and customer satisfaction in the commercial banks in Machakos Town. Methodology: The study adopted descriptive survey design. The target population was 82 commercial bank customers in Machakos Town. Primary data was collected through use of structured questionnaires. Descriptive statistics included frequency, mean and standard deviation. Simple regression modeling was used to aid in data analysis. Results: Research findings revealed that F statistic of model 1 was 33.236(p=.000). This portrayed that the influence of service quality aspect of customer retention strategies on customer satisfaction was statistically significant at 95% confidence level for (p<.05). Hence this model was suitable to estimate customer satisfaction amongst the five commercial banks in Machakos town. Adjusted R2 was of .648 which implies that customer retention strategies explained 64.8% of the variations in customer satisfaction. Bank retention strategies had statistically significant influence on customer satisfaction with a one unit change leading to .384(p=.000) change in customer satisfaction. Unique contribution to theory, practice and policy: The study recommended that management need to improve on efficiency in its operations regarding the customers and develop their products fully so as to satisfy their customers and control their product prices as well to be sure of customer retention. In addition, the bank should mitigate the risk of customer loss by ensuring that policies are put in place maintain product diversification.